PELAKSANAAN PROGRAM PENDAMPINGAN LANSIA DI PANTI SOSIAL TRESNA WERDHA KARITAS CIMAHI - Sipayung, Ester Elisabeth (2014)
This research examines how compliance with the implementation of mentoring programs mentoring elderly in Workhouses Tresna Werdha Karitas. This research aims to know and obtain data on the implementation of mentoring in the elderly. The method used is descriptive method, with samples of a total of as many as 20 people. This research instrument using the likert scale and the interview. The results of this research show that the implementation of mentoring related to daily activities, mentoring programs for compliance with the implementation of the programme of mentoring, and tasks as well as the responsibility of the Board generally has done very well. The recommendations of the research results is expected to further enhance the escort duties and responsibilities in caring for and maintaining the health and elderly needs effectively and efficiently